Performance Assessment Based on Balance Scorecard in Francial Company PT. Otewe Maju Bersama - Desy Jayanti; Rimi Gusliana Mais; iman Sofian Suriawinata (BPJP - STEI, 2020)
This study aims to determine the performance of the BSC in the franchise company PT. Otewe Maju Bersama is based on a financial perspective, customer perspective, internal business process perspective as well as learning and growth perspective. This research method is a quantitative method with a case study approach. The study population is all branches of the franchise PT. Otewe Maju Bersama, amounting to 55 branches. Sampling is done by using purposive sampling technique which is a type of non-random sample selection for which information is obtained using certain considerations. The respondents chosen in this study were employees of PT. Otewe Maju Bersama and restaurant customers owned by PT. Otewe Forward Together. The results of this study indicate that performance in a financial perspective is good. This is seen because it has been able to increase the percentage of growth in accordance with the plans made by the company. From the customer's perspective that performance is said to be good, this is seen from the average value of statement items on the customer's perspective that shows the answers of customer respondents tend to agree with answers and strongly agree and have good interpretation. The level of customer satisfaction and trust reaches 94%. While from the perspective of internal business processes it is said to be good, this can be seen from the Innovations made by Ropang OTW always trying to keep abreast of market developments and the desires of customers and companies always make efforts through structuring strategies in business and management. Innovations are made to provide excellent service for customers. As well as learning and growth perspectives are good, this can be seen from the average value of statement items on the learning and growth perspective which shows respondents' answers tend to be with answers agree and strongly agree.